Pengalaman Perawat Saat Terkonfirmasi Covid-19 Di Rumah Sakit Dokter H. Mochammad Ansari Saleh Banjarmasin - Iswanti Iswanti; Bahrul Ilmi; Muhammad Syafwani (Ridwan Institute, 2021)
The purpose of thestudy was to explore the experience of nurses who worked in the hospital doctor H. Mochammad Ansari Saleh Banjarmasin when confirmed COVID-19. Qualitative data was obtained through in-depth interviews on seven nurses at the hospital. This research uses qualitative research method with phenomenological approach, which aims to identify and explore nurse experience when confirmed COVID-19. There were seven respondents involved in the study. These seven respondents were nurses who treated COVID-19 confirmed patients who were still working in the COVID-19 room after being declared cured of COVID-19. The results found 6 main themes, namely: 1) COVID-19 transmission process; 2) Reasons for performing diagnostic checks; 3) Experiencing symptoms of COVID-19; 4) Experiencing symptoms of drug side effects; 5) Actions taken after COVID-19 is confirmed; and 6) Find information about COVID-19. When confirmed COVID-19 according to most participants is a not very overwhelming experience can be, but they still experience anxiety despite having prepared physically and mentally COVID-19 disease is experienced including in a mild degree, so the chance of recovery is very great. The experience of nurses when confirmed by COVID-19 according to most participants is not very overwhelming experience, but when confirmed COVID-19 they still experience anxiety even though they stated before it happened they were already preparing physically and mentally if at any time they were confirmed COVID-19.